2014
DOI: 10.7717/peerj.479
|View full text |Cite
|
Sign up to set email alerts
|

Local domestication of lactic acid bacteria via cassava beer fermentation

Abstract: Cassava beer, or chicha, is typically consumed daily by the indigenous Shuar people of the Ecuadorian Amazon. This traditional beverage made from cassava tuber (Manihot esculenta) is thought to improve nutritional quality and flavor while extending shelf life in a tropical climate. Bacteria responsible for chicha fermentation could be a source of microbes for the human microbiome, but little is known regarding the microbiology of chicha. We investigated bacterial community composition of chicha batches using I… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 52 publications
0
29
2
Order By: Relevance
“…Also, these bacteria are known to form biofilm (Ajdic, et al, 2002;Li, et al, 2002) which may change bacterial location and reduction of planktonic cells. Additionally, unlike our study Colehour, et al, 2014 found predominance of L. reuteri which is known to antagonize S. salivarius (Nikawa, et al, 2004;Corby, et al, 2005). Similar to previous studies (Colehour, et al, 2014;Elizaquivel, et al, 2010;Puerari, et al, 2015), Lactobacillus was a dominant genus of lactic bacteria in chicha found in both culture dependent and independent assessments.…”
Section: Discusioncontrasting
confidence: 87%
See 2 more Smart Citations
“…Also, these bacteria are known to form biofilm (Ajdic, et al, 2002;Li, et al, 2002) which may change bacterial location and reduction of planktonic cells. Additionally, unlike our study Colehour, et al, 2014 found predominance of L. reuteri which is known to antagonize S. salivarius (Nikawa, et al, 2004;Corby, et al, 2005). Similar to previous studies (Colehour, et al, 2014;Elizaquivel, et al, 2010;Puerari, et al, 2015), Lactobacillus was a dominant genus of lactic bacteria in chicha found in both culture dependent and independent assessments.…”
Section: Discusioncontrasting
confidence: 87%
“…A recent study failed to detect S. mutans and S. salivarius in chicha prepared with chewed cassava in Ecuador (Colehour, et al, 2014). The disagreement between both studies may result from differences in samples in both studies ;Colehour, et al, 2014 collected beers that were fermenting for 4 days while we collected samples that were fermenting for 3 days.…”
Section: Discusionmentioning
confidence: 94%
See 1 more Smart Citation
“…The difference in the carbohydrate content might be due to the preliminary loss of soluble carbohydrate in the previous unit processing of the cassava tubers. The reduction in the carbohydrate content from the garri samples might also be due to the fact that the isolated microorganisms have the tendency to utilize the garri sample as source of carbon source for their usage and sustainability (Colehour et al 2014, Oyeyiola et al 2014. Fufu (market C) was significantly higher (p<0.05) in moisture content of 72.25 % than all the other fermented cassava food products.…”
Section: Resultsmentioning
confidence: 99%
“…In recent times, food researchers have discovered new ways to use cassava. Some of the new products made from cassava are chips (Nambisan & Sundaresan, 1985;Vitrac, Dufour, Trystram, & Raoult-Wack, 2001), fermented beer (Colehour et al, 2014), bread (Pasqualone et al, 2010), cake (Sanful & Darko, 2010), tapioca (Adebowale, Sanni, Awonorin, Daniel, & Kuye, 2007;Sanni, Atere, & Kuye, 1997), biofuel (Hu, Tan, & Pu, 2006;Nguyen, Gheewala, & Garivait, 2007;Papong & Malakul, 2010), and medicine (La Frano, Woodhouse, Burnett, & Burri, 2013). Cassava, when dried to a powdery (or pearly) extract, is called tapioca; its fermented, flaky version is named "garri" or "gari".…”
Section: Introductionmentioning
confidence: 99%